2001
DOI: 10.1186/1471-2199-2-5
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of CD5 expression in murine T cells

Abstract: Background: CD5 is a pan-T cell surface marker that is also present on a subset of B cells, B-1a cells.Functional and developmental subsets of T cells express characteristic CD5 levels that vary over roughly a 30-fold range. Previous investigators have cloned a 1.7 Kb fragment containing the CD5 promoter and showed that it can confer similar lymphocyte-specific expression pattern as observed for endogenous CD5 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In contrast, HVEM engagement increased phosphorylation of mitogen-activated protein kinase (MAPK) kinase (MEK) (Figure 4E). MEK activation can increase expression of E26 avian leukemia oncogene 1 (ETS1) as well as decrease an expression of transcription factor 3 (TCF-3 also known as E2A or E47), correspondingly, positive and negative regulators of Cd5 expression (Khanna et al, 2011; Page et al, 2004; Paumelle et al, 2002; Tung et al, 2001; Yang et al, 2004). We found a decreased expression of E2A (E47) and an increased expression and abundance of ETS1 in developing CD5 hi T cells, consistent with their specific functions in transcriptional regulation of Cd5 expression (Figure 4F–H).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, HVEM engagement increased phosphorylation of mitogen-activated protein kinase (MAPK) kinase (MEK) (Figure 4E). MEK activation can increase expression of E26 avian leukemia oncogene 1 (ETS1) as well as decrease an expression of transcription factor 3 (TCF-3 also known as E2A or E47), correspondingly, positive and negative regulators of Cd5 expression (Khanna et al, 2011; Page et al, 2004; Paumelle et al, 2002; Tung et al, 2001; Yang et al, 2004). We found a decreased expression of E2A (E47) and an increased expression and abundance of ETS1 in developing CD5 hi T cells, consistent with their specific functions in transcriptional regulation of Cd5 expression (Figure 4F–H).…”
Section: Resultsmentioning
confidence: 99%
“…Potential targets of Ets1, including CD5 or TCR genes, have been identified in vitro ( Ho et al, 1990 ; Prosser et al, 1992 ; Tung et al, 2001 ; Arman et al, 2004 ) and in a large-scale ChIP study of Ets1 binding in the Jurkat human T cell line ( Hollenhorst et al, 2007 ). However, only a few genes, including IFN-γ ( Grenningloh et al, 2005 ) and Runx3 (this study) have been shown to both recruit and require Ets1 for their expression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its tissuerestricted distribution (21), Elf-1 is a likely partner in the concerted regulation of the mCD3␦ gene. Moreover, Elf-1 has been shown to play a critical role in regulation of other T cell-specific genes, including CD3, CD4, and CD5 (22)(23)(24)(25). Studies with Ets-1-deficient mice showed defects in mature T cells but no defect in T cell development.…”
Section: Discussionmentioning
confidence: 99%